The Implementation of Contingent Valuation Method for Waste Management at Telaga Ngebel, Ponorogo, Indonesia: A Novel Approach to Ecotourism Waste Processing House - Gravitiani, Evi; Ratnadewati, Ainina; Widiastuti, Nur (Nature environment and pollution technology, 2025)
The increase in the number of visitors to the tourism sector has a positive impact on the economy of the surrounding merchants. However, it also creates negative externalities through increased waste generation. The generation of unresolved waste will disrupt the function of the environment. Ecotourism Waste Management is one way to handle waste from sellers and tourists by collecting, processing, and selling processed products. The “Waste Treatment House” manages sales proceeds from and for sellers with a profit-sharing system. This effort requires the willingness to pay (WTP) sellers for waste management. This study aims to determine the amount of waste retribution and the factors that influence it. The data used in this study were primary data of 104 sellers in Telaga Ngebel Area, Ponorogo, Indonesia, and were processed using ordinary least squares (OLS) regression and descriptive analysis. WTP value is influenced by age, monthly expenses, number of dependents, operating hours, and length of business. The products produced through the program are organic waste processed into compost and fish feed, while inorganic waste is processed into handicrafts. Finally, selling processed waste products and the proceeds from these sales are used to increase merchant empowerment through revenue sharing and savings and loan products. This study has limited secondary data, namely information about the sustainability of waste management that has been carried out and the exact number of sellers in the area around Telaga Ngebel.